Implementasi Kebijakan Prioritas Penggunaan Dana Desa pada Pemerintah Desa Lanjut Kecamatan Singkep Pesisir Kabupaten Lingga Tahun 2024 - Ridho Ridho; Yudhanto Satyagraha Adiputra; Eki Darmawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the implementation of the priority policy for the use of Village Fund in 2024 in Lanjut Village, Singkep Pesisir District, Lingga Regency. The main focus of this study is how the national policy on the priority use of Village Fund is practically implemented at the village level, including the supporting and inhibiting factors. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document studies. The analytical model used refers to the implementation theory of Van Metter and Van Horn, which includes six main variables: policy objectives and size, resources, characteristics of the implementing agents, disposition of the implementers, communication, and social, economic, and political conditions. The results of the study show that the policy implementation was carried out participatively through village deliberation forums, involving the community in every stage of planning and decision-making. Several priority programs, such as Direct Cash Assistance (BLT), food security programs, and reducing stunting, were successfully realized, providing direct benefits to the village community. However, the implementation of this policy is not without challenges. Some identified obstacles include limited use of information technology to support transparency and efficiency, the readiness of human resources (HR) for implementation that still needs improvement, and the capacity of village institutions that has not yet reached its full potential. Despite these challenges, the overall implementation of the Village Fund policy in Lanjut Village can be considered relatively effective, given the successful realization of various priority programs that support participatory, transparent, and sustainable village governance. The conclusion of this study is that, although there are obstacles, the Village Fund policy in Lanjut Village has provided positive impacts on the community's welfare.